Adsorptive Anodic Stripping Voltammetric Determination of Atropine in Urine Sample. Issue 3 (18th March 2021) - Torrarit, Kamonchanok; Promsuwan, Kiattisak; Soleh, Asamee; Saisahas, Kasrin; Thiagchanya, Adul; Phonchai, Apichai; Limbut, Warakorn
Abstract : Overdose of atropine usually leads to heart failure and death and has long been used as a method of murder. We propose a simple electrochemical approach for atropine sensing using an electrode modified with nafion/polycarboxylate functionalized graphene nanoflakes (Nf/p-GNF/E). The polycarboxylate functionalized graphene nanoflakes were characterized by SEM, FT-IR, and electrochemical techniques. The electrochemical behavior and determination of atropine at the Nf/p-GNF/E were examined using cyclic voltammetry (CV) and adsorptive anodic stripping voltammetry (AdASV). The amount of Nf/p-GNF drop-cast on the electrode, accumulation potential and time, and pH buffer were optimized. Under the optimized conditions, the modified electrode showed excellent electrochemical oxidation of atropine with a linear range from 6.0 × 10 −6 to 1.0 × 10 −4 mol L −1 and a detection limit of 1.9 × 10 −6 mol L −1 . The proposed sensor exhibited excellent repeatability (RSD < 2.8%), reproducibility (RSD < 2.7%), and good resistance to interference from glucose, fructose, dopamine, uric acid, and ascorbic acid. The sensor was applied to determine atropine in urine samples and the results were in good agreement with results from the spectrophotometric analysis.